RHEOLOGICAL BEHAVIOUR OF KAOLIN/TALC/ALUMINA SUSPENSIONS FOR MANUFACTURING CORDIERITE FOAMS - Rodrigues Neto J.B.; Moreno R. (My University, 2007)
This paper deals with the preparation and rheological characterization of concentrated suspensions (40 vol.% solids) of mixtures of kaolin/talc/alumina to relative weight contents of 40/43.8/16.2, respectively. These concentrated suspensions were thixotropic and viscous, the rheological properties being largely influenced by a number of processing parameters, the most relevant being the nature and content of deflocculant and the pH value. Best results were obtained for a polyacrylic-based polyelectrolyte and pH 11. Green densities of 59% of TD were obtained. Dynamic and static sintering studies were performed and the analysis of the resulting phases was made by XRD. From these tests it was concluded that cordierite phase needed a thermal treatment of 1300 °C to be formed. The sintered slip cast materials have a large residual porosity because of the coarse particle size of the raw materials. Macroporous cordierite foams are obtained by impregnation of polyurethane foam into the optimized slip and heating at 1350 °C/1 h with a burning out step at 550 °C/30 min. © 2006 Elsevier B.V. All rights reserved.
Keywords: CORDIERITE; KAOLIN; RHEOLOGY; SUSPENSIONS; TALC